解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 22:32:48
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x)x=(?)解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x)x=(
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x)
16x-4x=3/5*(11-16x)+4x
8x=6.6-9.6x
17.6x=6.6
x=3/8
16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x)
12X+2/5(11-16X)-(11-16X)-4X=0
8X+22/5-32/5X-11+16X
88/5 X-33/5=0
X=3/8
解方程 16x=1+x
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
解方程:16x+1/5(11-16x)-4x=(11-16x)+4x-1/5(11-16x) x=(?)
解方程:3x(7-2x)-5x(2x-1)=16x(-x-3)+74
解方程:2x(x-2)-6x(x-1)=4x(1-x)+16
解方程 x-(1/5x+16)=32
解方程:32/x-4x+5/16=1
1+X/2-3+X/4=1+X/16-X-5/8 解方程
解方程:(5x-1)/3=(2x+1)/2-(2-x)/6 |5x+4解方程:(5x-1)/3=(2x+1)/2-(2-x)/6|5x+4|+2=8(0.3-30x)/0.3-6.5=3(5-2x)/0.05-11/2x=1+x/2+x/4+x/8+x/16
x÷4=11解方程.5x-17=73解方程.6.1-x=4.5解方程.4x+16=100解方程.(x+2)÷5=6.2解方程.4x+7x=12.1解方程.5x-2.1×4=11.6解方程.8x-3x=3.5解方程.
解方程:3/8x+x/4=16 1/5x+x/10=2 3x/11-x/10=7怎么解?
解方程:3/8x+x/4=16 1/5x+x/10=2 3x/11-x/10=7怎么解
解方程:(1)2/(x+1)+3/(x-1)=6/(x^2-6) (2)x-2/(x+2)-16/(x^2-4)=x+2/(x-2) (3)3/x+6/(x-1)=x+5/(x^2-x)
(1)解方程x(16x-5)-(4x+1)(4x-1)=112.解不等式2x(x-1)-x(2x-5)
x-20/3+x-18/5+x-16/7+x-14/9+x-12/11解方程
x(16x-5)-(4x+1)(4x-1)=11 3x(x+2)+2(x+1)(x-1)=5(x^2+8)解方程
5+6/(x-16)=(2x-1)/(x+4)-(3x-1)/(4-x)解方程
解方程 5+96/X²-16=2X-1/4+X - 3X-1/4-X